Real-time monitoring and control of flow rate in transportation pipelines using Matlab-based interactive GUI and PID controller - S. Vijayalakshmi; C. Anuradha; R. C. Ilambirai; Viswanathan Ganesh (Institute of Advanced Engineering and Science, 2020)
In this paper, a Matlab based GUI and Propotinal Integral Dervative (PID) controller is designed to automatically regulate the flow-rate of the circulating fluid. When fluids are transported over long distances, the pressure and flow rate have to be monitored remotely in a control room. Using an HMI or Control Panels the flow rate can be increased or decreased to compensate for pressure drops or disturbances. This paper attempts to demonstrate such an Industrial Control Operation in a scaled-down environment. A Graphical User Interface or GUI is constructed which enables the Operator to monitor, as well as control an electronically actuated Control Valve which can efficiently regulate the flow-rate. Automatic operations have also been implemented using a PID controller algorithm, which tries to track the Set-point in Real-time.